On the stability of the distribution íunction o f the composed random variables by their index random variable - Bao, Nguyen Huu (VNU Journal of Science: Mathematics - Physics; Vol 23 No 2, 2007)
b s t r a c t . Let us consider the composed random variable TỊ = Y l k = 1 &> vvhere — are independent iđentically distributed random variables and V is a positivc value random, independent of all In [1] and [2], we gave some the stabilities of the distribution function o f 7] in the following sense: the small changes in the distribution íunction o f Ẹk only lcad to the small changes in the distribution íunction o f TỊ. In the paper, we investigate the distribution íunction o f TỊ vvhen we have the small changes of the distribution of V.